2-Hydroxyisobutyric acid targeted binding to MT-ND3 boosts mitochondrial respiratory chain homeostasis in hippocampus to rescue diabetic cognitive impairment - Minzhen Xie; Siqi Gu; Yan Liu; Haolin Yang; Yuqi Wang; Wei Yin; Yang Hong; Wanying Lu; Chengbing He; Lin Li; Limin Zhao; Jianjia Zhang; et al. (Redox Biology)
Background: The prevalence of diabetic cognitive impairment (DCI) is significant, some studies have shown that it is related to mitochondrial respiratory chain homeostasis, but the specific mechanism is not clear. 2-hydroxyisobutyric acid (2-HIBA) is a novel short-chain fatty acid with potential applications in the treatment of metabolic diseases because it can regulate mitochondrial disorders. Our aim was to explore a novel mechanism of action for 2-HIBA in the treatment of DCI in mitochondrial respiratory chain homeostasis. Methods: Metabolic substances and differentially active metabolic pathways in the serum of diseased mice were identified based on multi-omics analysis. The nanoLC-Obitrap-MS technology was utilized to detect the content of selected small molecules with differential metabolic activity in the hippocampus and mitochondria of mice to evaluate their permeability through the blood-brain barrier (BBB) and outer mitochondrial membrane. A combination of behavioral, proteomic, and molecular biology approaches was used to explore specific regulatory mechanisms and identify potential pharmacological targets. Additionally, using techniques such as protein thermal shift, drug affinity responsive target stability (DARTS), hydrolase stability, and surface plasmon resonance (SPR) experiments, we demonstrated the direct binding effects of small molecule metabolites with protein targets. Results: 2-HIBA was found to directly ameliorate cognitive dysfunction in db/db mice by penetrating the blood-brain barrier and reversing the decrease in the protein content of NADH dehydrogenase 3 (MT-ND3) in the hippocampus through direct binding to ND3. This action helps maintain the stability of NAD+/NADH and regulate the mitochondrial respiratory chain balance. Furthermore, a combined medication plant agonist of 2-HIBA can enhance the expression of MT-ND3, thereby improving cognitive dysfunction in mice. Conclusion: MT-ND3 is a crucial target for improving diabetic cognitive dysfunction, and 2-HIBA can directly bind to the MT-ND3 protein to alleviate the functional impairment of the mitochondrial respiratory chain in mice to treat DCI.